2003
DOI: 10.1093/pasj/55.5.1005
|View full text |Cite
|
Sign up to set email alerts
|

A Differential Abundance Analysis of the Wide Binary Pair HD 219542 A and B

Abstract: The abundances of 22 elements (Li through Zr) in the A and B components of the visual pair HD 219542 were determined and compared using a differential analysis technique. Both components were found to be metal rich, $[\mathrm{Fe/H}] = +0.13$, in the brighter component (A) and $[\mathrm{Fe/H}] = +0.08$ in the fainter component (B). The abundances of three elements (Sc, Ti, and Fe) are definitely higher (by 0.05 dex) in component A than in component B. On the other hand, both components have nearly identical abu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 28 publications
4
14
0
Order By: Relevance
“…They found (T eff , log g, ξ, 5830, 4.45, 0.95, 0.13) and (5600, 4.40, 0.90, 0.08) for HD 219542A and B respectively. Our parameters for the primary are fairly similar to their values, while their temperature differences is larger by 62 K. However, we note that the statistical error quoted by Sadakane et al (2003) for the temperature difference is 42 K (30 K for each star). Furthermore, we note some inconsistencies in the parameters they derived.…”
Section: Comparison With Paper I and Other Literature Datasupporting
confidence: 77%
See 3 more Smart Citations
“…They found (T eff , log g, ξ, 5830, 4.45, 0.95, 0.13) and (5600, 4.40, 0.90, 0.08) for HD 219542A and B respectively. Our parameters for the primary are fairly similar to their values, while their temperature differences is larger by 62 K. However, we note that the statistical error quoted by Sadakane et al (2003) for the temperature difference is 42 K (30 K for each star). Furthermore, we note some inconsistencies in the parameters they derived.…”
Section: Comparison With Paper I and Other Literature Datasupporting
confidence: 77%
“…As a check that the discrepancy is not due to EW measurements, we analyzed our data using the Sadakane et al (2003) atmospheric parameters, and found very similar abundance differences than obtained by them, and the Sadakane et al (2003) EW using our technique. The latter test gives a temperature difference 27 K larger than ours (195 vs. 168 K) and an abundance difference of 0.012 dex.…”
Section: Comparison With Paper I and Other Literature Datasupporting
confidence: 56%
See 2 more Smart Citations
“…Such a slightly metal-rich nature of HD 219542 A compared to B has also recently been confirmed by Sadakane et al (2003), who concluded [Fe/H] A − [Fe/H] B = + 0.05 dex. From a quantitative point of view, however, the extent of the difference is discrepant ( + 0.09 and + 0.05) between these two studies, and the discordance is larger than their estimated errors, 2 which makes us wonder which is more reliable and whether an accuracy on the order of 2 Although Sadakane et al (2003) presented only the standard deviation values and did not discuss in sufficient detail about the error involved in the mean difference of + 0.05 dex they derived, the random error for the mean abundance difference from Fe I lines may be estimated as σ √ N = 0.032/ √ 46 0.005, which is comparable to that of Gratton et al (2001) (i.e., pure random error of 0.006 without including the effect of parameter uncertainties). However, the actual uncertainties may be much larger, when ambiguities in the atmospheric parameters are taken into account, as discussed in section 5.…”
Section: Introductionsupporting
confidence: 65%